2022
DOI: 10.3390/cancers14194925
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MARCKS in Metastasis and Treatment Resistance of Solid Tumors

Abstract: The myristoylated alanine-rich C-kinase substrate (MARCKS) is a membrane-associated protein kinase C (PKC) substrate ubiquitously expressed in eukaryotic cells. MARCKS plays important roles in multiple cellular processes, including cell adhesion and motility, mucin secretion, exocytosis, and inflammatory response. Aberrant MARCKS signaling has been observed in the development and progression of multiple cancer types. In addition, MARCKS facilitates cancer metastasis through modulating cancer cell migration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…While our report newly demonstrates that one of the major effect of NMT1 KO and PCLX-001 treatment is on mitochondrial proteins, we showed that NMT inhibition also profoundly affected numerous myristoylated signaling proteins in addition to SFKs, including oncogenes (ABL2 [ 66 ], MARCKS [ 67 ], BASP1 [ 68 ]), membrane lipid raft proteins including flotillin-2 [ 69 ] and raftlin [ 70 ], and proteins involved in vesicular transport (e.g., Arf1-6) [ 71 ] (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 83%
“…While our report newly demonstrates that one of the major effect of NMT1 KO and PCLX-001 treatment is on mitochondrial proteins, we showed that NMT inhibition also profoundly affected numerous myristoylated signaling proteins in addition to SFKs, including oncogenes (ABL2 [ 66 ], MARCKS [ 67 ], BASP1 [ 68 ]), membrane lipid raft proteins including flotillin-2 [ 69 ] and raftlin [ 70 ], and proteins involved in vesicular transport (e.g., Arf1-6) [ 71 ] (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 83%
“…As previously reported, MARCKS translocation was correlated with either PKC/RhoA-dependent PSD phosphorylation or calcium-dependent calmodulin binding [ 38 ], and we further analyzed the results shown in Fig. 6 A to filter potential proteins related to MARCKS translocation.…”
Section: Resultsmentioning
confidence: 93%
“…For instance, Wenzel T et al reported that CRC cells lacking MARCKS expression exhibit enhanced chemoresistance due to increased ABCB1 expression [ 58 ]; moreover, MARCKS protein expression levels are inversely correlated with GBM proliferation and intracranial xenograft growth rates in vivo [ 59 ]. In addition, the oncogenic roles of MARCKS in cancer proliferation, metastasis and chemoresistance have also been demonstrated [ 38 ]. The roles of MARCKS are strongly correlated with its subcellular location in cells, as membrane-located MARCKS interacts with PI [ 4 , 5 ]P 2 ; once MARCKS is translocated into the cytoplasm, PI [ 4 , 5 ]P 2 is released from MARCKS to further interact with other proteins and activate downstream pathways, such as the PI3K/AKT/mTOR pathway [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…105 Additionally, we have observed an elevation in myristoylated alanine-rich C-kinase substrate (MARCKS), which facilitates cancer metastasis through modulating cancer cell migration and invasion, in cells on collagen IV-coated surfaces. 106 We further treated cells with selective inhibitors of AXL (XL184 and R428) and the treatments successfully reduced cell motility on collagen IV but not collagen I (Fig. 8B and C).…”
Section: Lab On a Chip Papermentioning
confidence: 95%